Bycatch composition of cutlassfish trawlers during fishing season in Bushehr and Hormozgan, Persian Gulf, Iran - AHMAD FOULADI SABET; SEYED YOUSEF PAIGHAMBARI; MOJTABA POULADI; HADI RAEISI; REZA ABBASPOUR NADERI (Society for Indonesian Biodiversity, 2018)
Fouladi Sabet A, Paighambari SY, Pouladi M, Raeisi H, Abbaspour Naderi R. 2018. Bycatch composition of cutlassfish trawlers during fishing season in Bushehr and Hormozgan, Persian Gulf, Iran. Biodiversitas 19: 2275-2282. This investigation was conducted to determine the bycatch composition of cutlassfish (Trichiurus lepturus) trawlers in Bushehr and Hormozgan waters during fishing season 2013. Data collection was carried out in the summer for Bushehr and in the autumn for Hormozgan province for one month. All trawler vessels were equipped with a 36 m head rope and 75 mm stretched mesh size in the codend and 90 to 200 mm stretched mesh size in the panel. 47 species included 35 species of teleosts, 9 species of elasmobranches and 3 species of invertebrates were identified in Bushehr. Also, 48 species included 38 species of teleosts, 7 species of elasmobranches and 3 species of invertebrates were identified in Hormozgan. The weight and numerical averages of bycatch species were 25.41 (kg h-1) and 205.9 (n h-1) in Bushehr, and 92.58 (kg h-1) and 440.4 (n h-1) in Hormozagan. I. megaloptera, S. tumbil, N. japonicus, D. acuta, C. sexfasciatus, L. equulus in Bushehr and P. sextarius, I. megalopteran, M. cinereus, P. macrophthalmus, N. japonicus and S. tumbil in Hormozgan had highest catch weight. Based on the weight and number, PCA and nMDS methods were indicative of two different assemblages in hunting places. Furthermore, ANOSIM similarity analysis confirmed the results of PCA and nMDS and showed a significant difference in the catch composition of two fishing zones.